2021
DOI: 10.3390/life11060558
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Total Fishmeal Replacement by Arthrospira platensis on the Microbiome of African Catfish (Clarias gariepinus)

Abstract: An increasing number of fishmeal supplements are becoming the focus of aquaculture research, with a special emphasis on microalgae/cyanobacteria such as spirulina being considered as sustainable alternatives. New feed ingredients can have a far-reaching impact on the intestinal microbiome and therefore play an important role in the development and the health of fish. However, the influence of these alternatives on the microbiome is largely unknown. We undertook a 10 weeks feeding experiment on 120 African catf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…However, dietary protein hydrolysates supplementation significantly reduced the diversity of the intestine microbial community, which was in line with previous studies in largemouth bass and gilthead seabream ( 94 ; 95 ). Previous studies have revealed that Plesiomonas is a normal inhabitant of the fish gut ( 96 ), and this genus was also the most dominant microbes observed in African Catfish ( 97 ). The antimicrobial effect of Plesiomonas has been well clarified ( 98 ), and therefore, the decreased inflammatory response of larvae in the PH100 group may have been also partly due to the increased relative abundance of Plesiomonas .…”
Section: Discussionmentioning
confidence: 99%
“…However, dietary protein hydrolysates supplementation significantly reduced the diversity of the intestine microbial community, which was in line with previous studies in largemouth bass and gilthead seabream ( 94 ; 95 ). Previous studies have revealed that Plesiomonas is a normal inhabitant of the fish gut ( 96 ), and this genus was also the most dominant microbes observed in African Catfish ( 97 ). The antimicrobial effect of Plesiomonas has been well clarified ( 98 ), and therefore, the decreased inflammatory response of larvae in the PH100 group may have been also partly due to the increased relative abundance of Plesiomonas .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported better feed conversion efficiency in Nile tilapia raised in aquaponics than in those raised in conventional fishponds (Amin et al, 2021; Shaw et al, 2022; Strand et al, 2007). An important observation in the aquaponic fish tank was the presence of slimy cyanobacteria (Figure 5), which increased with time and has been reported to significantly contribute to more than 10% of fish protein intake and affect their gut microbiome(Rosenau et al, 2021). Changes in the gut microbiome composition have profound effects on the physiological and molecular functions of C. gariepinus (Adejonwo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the digestibility for both diets was high, but the feed conversion ratio was increased for spirulina-fed rainbow trout and brook trout and resulted in significantly lower growth rates in all species. A subsequent investigation of the intestinal microbiome in African catfish, using 16S rRNA sequencing, found only slight changes for some bacterial genus, but the overall microbial community structure was not affected by spirulina-diet [ 26 ].…”
Section: Spirulina In Fish Feedmentioning
confidence: 99%